Towns as the Recruitment Base to Mercenaries During the Reign of the Last Jagiellons - Bołdyrew, Aleksander (City and War, 2022)
The newest research of mercenary armies at the time of the Jagiellons shows among others the social-territorial structure of the these forces’ soldiers. In that one knows towns were more important element in the soldiers’ recruitment system than one has believed hitherto. However, from wider point of view, the enhancement of the townsfolk’s participation in the army instead of the peasants did not imply the growth of the towns’ standing in the state structures. The analyse of these questions leads to the conclusion that the standing of the Kingdom of Poland towns was low, what had consequences not only in the military field, but also translate to the economic and politic functioning of the state. These issues were discussed in the connection with the time of the last Jagiellons’ reign, using the sources unheralded until now (registers of the Polish Crown army from the Sigismund II Augustus’s reign time stored away in the Central Archives of Historical Records in Warsaw).